2006
DOI: 10.1177/106591290605900106
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Recent Changes in the Partisan Identifications of Southern Whites

Abstract: Scholars of southern partisan change have been reluctant to proclaim a realignment among southern whites. Despite a Republican advantage in presidential elections, a Democratic advantage continued to persist in party identifications. However, in the 1990s a Republican advantage in party identifications emerged, one that has persisted throughout the decade. Indeed in 2000 a majority of southern whites held Republican party identifications, while only one in three southern whites held Democratic identifications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 43 publications
1
20
1
Order By: Relevance
“…As was pointed out above, several studies in the 1970s and 1980s found that seniors were more Democratic than baby boomers. One explanation for the difference in the findings of earlier research and this study probably is the increasing tendency for southerners to bring their party identification into alignment with the ideological orientation (Knuckey 2001;2006). In the 1970s, older white voters, even those in their 40s or 50s, may have retained their strong Democratic identification, which was established during the Solid South era, even though they were more conservative than baby boomers, and even though they may have voted for Republican presidential candidates.…”
Section: ! 57contrasting
confidence: 52%
“…As was pointed out above, several studies in the 1970s and 1980s found that seniors were more Democratic than baby boomers. One explanation for the difference in the findings of earlier research and this study probably is the increasing tendency for southerners to bring their party identification into alignment with the ideological orientation (Knuckey 2001;2006). In the 1970s, older white voters, even those in their 40s or 50s, may have retained their strong Democratic identification, which was established during the Solid South era, even though they were more conservative than baby boomers, and even though they may have voted for Republican presidential candidates.…”
Section: ! 57contrasting
confidence: 52%
“…David Lublin (2004) documented a historical shift toward the Republicans beginning in the 1970s and provided evidence that most of the pro‐GOP voting was a result of an increasingly class‐based two‐party system that emerged in the South and that began to mirror the party systems in nonsouthern states. Similarly to Lublin, Abramowitz and Saunders (1998) saw the South as following a national trend toward ideological polarization of the two parties, a notion confirmed by Hood, Kidd, and Morris (1999), Knuckey (2006), and Knotts and others (2005).…”
Section: Different Interpretations Of the 1994 Elections In The Southmentioning
confidence: 86%
“…As noted earlier, other researchers have attempted to explain Republican Party identification among white southerners, testing a number of hypotheses with differing variables. On one hand, Lublin (2004), Abramowitz and Saunders (1998), and Knuckey (2006), for example, all believe that class‐based ideological positions regarding the role of the government in regulating the economy had become more important in explaining partisanship and partisan voting behavior in national‐level politics as well as in politics in the South in the 1980s and 1990s. On the other hand, Knuckey (2006) also expressed the belief that there was a tendency of white southerners to base their partisanship on racial resentment and attitudes toward abortion, and Knotts and others (2005) also found that attitudes toward abortion and regarding women's equality also grew in importance in the 1990s relative to the 1980s in the South.…”
Section: White Southerners and Party Identification Before 1994mentioning
confidence: 99%
See 1 more Smart Citation
“…The other independent variables are retrospective evaluations, represented by President Bush's job approval ratings (Fiorina 1981), religious values, as represented by church attendance (Green et al 2002;Green et al 2003;Knuckey 2006;Schneider 1998;Smith 1997;Oldfield 1996), economic class represented by education level (Brewer and Stonecash 2001;Shafer and Johnston 2006), and age (Schuman et al 1997;Virtanen and Huddy 1998). I control for the influences of ethnicity by including a dummy variable representing white-Hispanics.…”
Section: Data Sets Measurement and Modelmentioning
confidence: 99%